Size structure of Antarctic krill inferred from samples of Pygoscelid penguin diets and those collected by the commercial krill fishery - Juares, Mariana Alejandra; Grech, Marta Gladys; Casaux, Ricardo Jorge; Negrete, Javier; Fógel, Jazmín; Coria, Néstor Rubén; Santos, Maria Mercedes (Marine Biology)
In the Antarctic Peninsula, during the chick-rearing period Adélie (Pygoscelis adeliae) and gentoo (P. papua) penguins feed primarily on Antarctic krill (Euphausia superba), which is also exploited by the commercial fishery. Krill length and proportion of juvenile krill consumed by these predators that breed at Stranger Point, South Shetland Islands (from 2007/2008 to 2015/2016), and those collected by the krill fishery in the Mar de la Flota/Bransfield Strait (from 2009/2010 to 2015/2016) were compared to evaluate the potential of each data source as an indicator of changes in the size composition and so, in the demographic structure of the krill population. Overall, the mean krill size taken by gentoo penguins was larger than that ingested by Adélie penguins, which consumed higher proportions of juvenile (≤ 35 mm) and one-year-old (≤ 25 mm) krill. Although the krill size caught by the fishery was statistically similar to that taken by both penguin species, there were differences in the frequency distributions of krill size among the three databases. Furthermore, when only adult krill (> 35 mm) was considered, the three sources of krill data showed a similar inter-annual variation in the availability of adult krill cohorts. Our findings suggest that each database analysed here can potentially provide different information (although complementary) about krill size composition. In addition, inter-annual fluctuations in the smaller size classes of krill likely reflect their first year of recruitment and, therefore, may be used as an indicator of shifts in local krill availability. Fil: Juares, Mariana Alejandra. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino. Departamento de Biología de Predadores Tope; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina Fil: Grech, Marta Gladys. Consejo Nacional de Investigaciones Científicas y ...